2020
DOI: 10.1016/j.molcel.2020.05.024
|View full text |Cite
|
Sign up to set email alerts
|

A Contaminant Impurity, Not Rigosertib, Is a Tubulin Binding Agent

Abstract: Highlights d Rigosertib does not bind directly to tubulin d Rigosertib dos not inhibit tubulin polymerization d Expression of TUBB L240F does not confer resistance to rigosertib d A small percentage of rigosertib-and BI2536-treated TUBB L240F cells undergo senescence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Initial findings described rigosertib as a multi-kinase signaling inhibitor with effects on PLK1, PI3K pathways, and the RAF-MEK-ERK pathway [7] , [30] , [31] , [32] , but the precise mechanism of action of rigosertib is still being debated [11] , [12] , [13] . Our results showing decreased pAKT (Ser473) and pERK1/2 (Thr202/Tyr204) levels indicate the involvement of the AKT and RAS signaling pathways in its mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial findings described rigosertib as a multi-kinase signaling inhibitor with effects on PLK1, PI3K pathways, and the RAF-MEK-ERK pathway [7] , [30] , [31] , [32] , but the precise mechanism of action of rigosertib is still being debated [11] , [12] , [13] . Our results showing decreased pAKT (Ser473) and pERK1/2 (Thr202/Tyr204) levels indicate the involvement of the AKT and RAS signaling pathways in its mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Rigosertib has also been proposed to function as a RAS mimetic by affecting the RAS-binding domain of RAS effector proteins, thereby inhibiting MEK-ERK signaling [10] . However, recent studies have shown that rigosertib functions as a microtubule-destabilizing agent [11] , therefore its precise mechanism(s) of action remain a matter of debate [12] , [13] . Nevertheless, rigosertib has shown anti-tumor effects in preclinical in vivo models of solid tumors including breast, pancreatic [6] , colorectal, and lung cancer [10] .…”
Section: Introductionmentioning
confidence: 99%
“…The stress MAP kinases phosphorylate components of the RAS pathway, including Raf family members and SOS1, a RAS guanine nucleotide exchange factor, which further decreases signaling through the RAS/RAF/MEK/ERK MAP kinase pathway (3). The mitotic stress induced by rigosertib may be due to the fact that rigosertib, or a degradation product of rigosertib, binds to an intradimer site between α-and β-tubulin in a manner similar to colchicine, which prevents microtubule growth (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…In certain experiments, BMDMs were pretreated with 20 nM rigosertib for 1 h as previously described. 15 , 16 , 17 Then these BMDMs were further treated with 100 ng/ml LPS, 20 µg/ml poly I:C or 10 µg/ml interleukin‐4 (IL‐4) for 12 or 24 h.…”
Section: Methodsmentioning
confidence: 99%